Systematic review of involving patients in the planning and development of health care. Issue 7375 (30th November 2002) - Crawford, Mike J; Rutter, Deborah; Manley, Catherine; Weaver, Timothy; Bhui, Kamaldeep; Fulop, Naomi; Tyrer, Peter
Abstract: Objective: To examine the effects of involving patients in the planning and development of health care. Data sources: Published and grey literature. Study selection: Systematic search for worldwide reports written in English between January 1966 and October 2000. Data extraction: Qualitative review of papers describing the effects of involving patients in the planning and development of health care. Results: Of 42 papers identified, 31 (74%) were case studies. Papers often described changes to services that were attributed to involving patients, including attempts to make services more accessible and producing information leaflets for patients. Changes in the attitudes of organisations to involving patients and positive responses from patients who took part in initiatives were also reported. Conclusions: Evidence supports the notion that involving patients has contributed to changes in the provision of services across a range of different settings. An evidence base for the effects on use of services, quality of care, satisfaction, or health of patients does not exist.